2002
DOI: 10.1079/ahrr200244
|View full text |Cite
|
Sign up to set email alerts
|

Campylobactercolonization in poultry: sources of infection and modes of transmission

Abstract: Since its recognition as a human pathogen in the early 1970s, Campylobacter jejuni has now emerged as the leading bacterial cause of food-borne gastroenteritis in developed countries. Poultry, particularly chickens, account for the majority of human infections caused by Campylobacter. Reduction or elimination of this pathogen in the poultry reservoir is an essential step in minimizing the public health problem; however, farm-based intervention measures are still not available because of the lack of understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
135
2
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 110 publications
(251 reference statements)
12
135
2
6
Order By: Relevance
“…Since its recognition as a human pathogen in the early 1970s, Campylobacter has now emerged as a leading bacterial cause of food-borne gastroenteritis in developed countries. Poultry, particularly chickens, account for the majority of human infections caused by Campylobacter (Sahin et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Since its recognition as a human pathogen in the early 1970s, Campylobacter has now emerged as a leading bacterial cause of food-borne gastroenteritis in developed countries. Poultry, particularly chickens, account for the majority of human infections caused by Campylobacter (Sahin et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Reduction or elimination of this pathogen in the poultry reservoir is an essential step in minimizing the public health problem. However, farm-based intervention measures are still not available because of the lack of understanding of the ecological aspects of C. jejuni on poultry farms and Sahin et al [141] have elaborately discussed the horizontal and vertical transmissions of Campylobacter infections affected by immune status of the poultry host and the environmental conditions in the production system. Eifert et al [36] compared various sampling techniques (cloacal swabs, faecal samples and environmental surface "drag" swabs) on 3, 5 and 7 weeks old poultry birds for presence of Arcobacter butzleri, a causal agent of human enteritis and found that environmental swabs recorded the highest percentage recovery, while intestinal tracts had none.…”
Section: Farmsmentioning
confidence: 99%
“…Colonisation with some bacterial species can also have major implications for the agricultural industry and human health [2,3] . However, the first few days post-hatch are characterised by immune system immaturity as cellular components of the adaptive response are in a naive state and therefore slow to respond to infectious agents [4] , leading to increased early mortality in environments of high pathogenic challenge.…”
Section: Introductionmentioning
confidence: 99%